1958
DOI: 10.1017/s0022029900009158
|View full text |Cite
|
Sign up to set email alerts
|

703. Cineradiographic observations on machine milking

Abstract: Milk is obtained from the teat during machine milking by the creation of a partial vacuum; the rate of flow is influenced by many factors including changes in the vacuum, the pulsation rate or ratio, alterations in the design or construction of the teat cup liner. Recent research relating to these problems has been reviewed by Dodd & Clough(i).The rate of milk flow or machine milking rate is usually expressed as the mean rate of flow from one or more teats over a specified period of milking. In this way it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1964
1964
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Milk fl ows from the teat when the liner is open. Milk fl ow is stopped when the closing liner applies suffi cient pressure to the distal end of the teat to occlude the teat canal (Ardran et al 1958;Mein 1992). Stopping the liner in its closed position, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Milk fl ows from the teat when the liner is open. Milk fl ow is stopped when the closing liner applies suffi cient pressure to the distal end of the teat to occlude the teat canal (Ardran et al 1958;Mein 1992). Stopping the liner in its closed position, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Radiography (Pier, Schalm & Hage, 1956) and cine radiography (Ardran, Kemp, Clough & Dodd, 1958) have been used very effectively to study the action of the teatcup liner and its effect on the teat. Now that transparent liners are more readily available, a simpler alternative for some studies may be cine photography using transparent shells and liners.…”
mentioning
confidence: 99%
“…Conventional milking studies using cineradiography (Ardran et al 1958) and cinephotography using transparent liners and shells (Mein et al 1974) showed that in each pulsation cycle milk flow through the teat orifice starts when the liner is about half open and ceases when the liner is about half closed. During conventional milking the liner readily opens when the pulsation chamber is evacuated, owing to milk and air returning to the expanding liners.…”
Section: Discussionmentioning
confidence: 99%